Lymphovascular invasion quantification could improve risk prediction of lymph node metastases in patients with submucosal (T1b) esophageal adenocarcinoma. Issue 9 (5th October 2021) - van de Ven, Steffi E. M.; Suzuki, Lucia; Gotink, Annieke W.; ten Kate, Fiebo J. C.; Nieboer, Daan; Weusten, Bas L. A. M.; Brosens, Lodewijk A. A.; van Hillegersberg, Richard; Alvarez Herrero, Lorenza; Seldenrijk, Cees A.; Alkhalaf, Alaa; Moll, Freek C. P.; et al.
Abstract: Aim: To quantify lymphovascular invasion (LVI) and to assess the prognostic value in patients with pT1b esophageal adenocarcinoma. Methods: In this nationwide, retrospective cohort study, patients were included if they were treated with surgery or endoscopic resection for pT1b esophageal adenocarcinoma. Primary endpoint was the presence of metastases, lymph node metastases, or distant metastases, in surgical resection specimens or during follow‐up. A prediction model to identify risk factors for metastases was developed and internally validated. Results: 248 patients were included. LVI was distributed as follows: no LVI ( n = 196; 79.0%), 1 LVI focus ( n = 16; 6.5%), 2–3 LVI foci ( n = 21; 8.5%) and ≥4 LVI foci ( n = 15; 6.0%). Seventy‐eight patients had metastases. The risk of metastases was increased for tumors with 2–3 LVI foci [subdistribution hazard ratio (SHR) 3.39, 95% confidence interval (CI) 2.10–5.47] and ≥4 LVI foci (SHR 3.81, 95% CI 2.37–6.10). The prediction model demonstrated a good discriminative ability ( c ‐statistic 0.81). Conclusion: The risk of metastases is higher when more LVI foci are present. Quantification of LVI could be useful for a more precise risk estimation of metastases. This model needs to be externally validated before implementation into clinical practice.